2020
DOI: 10.1002/rcr2.684
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of airway tear as a complication of silicone endobronchial stenting in bronchomalacia secondary to endobronchial tuberculosis

Abstract: Tracheobronchial stenosis due to tuberculosis (TSTB) is a potentially debilitating complication of endobronchial tuberculosis (EBTB). Endobronchial interventions including silicone stent insertion is an acceptable approach to improve quality of life among patients with TSTB. However, little is known about the optimal management strategy for patients with bronchomalacia secondary to EBTB (B-EBTB) and whether stent-related complication rates are higher among this group of patients. Herein, we report two patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Two of our patients with TSTB who developed rapid recurrence of symptoms post intervention had concurrent bronchomalacia (case 3 and case 6). Besides, airway intervention might be riskier in cases of bronchomalacia related to EBTB with reduced airway thickness and loss of airway cartilaginous support [24]. On the other hand, Shirit et al demonstrated that TSTB patients needing more than one session of endoscopic airway intervention will subsequently require more definitive treatment in the form of either airway stent insertion or airway surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…Two of our patients with TSTB who developed rapid recurrence of symptoms post intervention had concurrent bronchomalacia (case 3 and case 6). Besides, airway intervention might be riskier in cases of bronchomalacia related to EBTB with reduced airway thickness and loss of airway cartilaginous support [24]. On the other hand, Shirit et al demonstrated that TSTB patients needing more than one session of endoscopic airway intervention will subsequently require more definitive treatment in the form of either airway stent insertion or airway surgery [15].…”
Section: Discussionmentioning
confidence: 99%